The principle of legal certainty concerning the implementation of legalization according to the apostille convention viewed from an international civil law perspective - Triyana Dewi Minda Yuda (International Journal of Latin Notary, 2023)
The principle of legal certainty is a foundational principle in the field of international law. The law must possess clarity, predictability, and accessibility for all individuals. The Apostille Convention is a multinational agreement that streamlines the procedure of authenticating public documents for international use. This is achieved by eliminating the need for authentication by a diplomatic or consular officer. This research study investigates the concept of legal certainty within the framework of the Apostille Convention. In writing this legal research, the author uses the concept of legal research with a comparative approach to compare the application of Apostille in Indonesia with Apostille in other countries. According to the researcher, implementing the Apostille Convention, already underway in Indonesia, has yet to fulfil reasonable legal assurance regarding international private law. The reason is that international law has a different legal system and regulations; the HCCH organization, as an Apostille melting pot, still needs legal arrangements that apply to all convention countries equally. Indonesia has more documents that can be ratified in submitting an Apostille application, but not all countries are the same in confirming an Apostille document.